2018
DOI: 10.1186/s12885-018-4686-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of vitamin D on pathological complete response and survival following neoadjuvant chemotherapy for breast cancer: a retrospective study

Abstract: BackgroundThere has been interest in the potential benefit of vitamin D (VD) to improve breast cancer outcomes. Pre-clinical studies suggest VD enhances chemotherapy-induced cell death. Vitamin D deficiency was associated with not attaining a pathologic complete response (pCR) following neoadjuvant chemotherapy (NAC) for operable breast cancer. We report the impact of VD on pCR and survival in an expanded cohort.MethodsPatients from Iowa and Montpellier registries who had serum VD level measured before or duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…Patients treated with neo-adjuvant chemotherapy for early breast cancer in our institution between January 2005 and September 2013 were included in a clinico-pathological database [ 53 , 54 , 55 ]. The database follow-up has been updated and completed until March 2019.…”
Section: Methodsmentioning
confidence: 99%
“…Patients treated with neo-adjuvant chemotherapy for early breast cancer in our institution between January 2005 and September 2013 were included in a clinico-pathological database [ 53 , 54 , 55 ]. The database follow-up has been updated and completed until March 2019.…”
Section: Methodsmentioning
confidence: 99%
“…Viala et al, analyzed the level of vitamin D in breast cancer patients after surgery and during or after neoadjuvant chemotherapy [48]. They noted that deficiency in vitamin D (less than 20 ng/mL 25(OH)D in serum) was not associated with survival in the entire studied population of 327 women, but a positive trend was observed in TNBC cases and in the hormone receptor-positive/HER2-negative subgroup.…”
Section: Observational Studiesmentioning
confidence: 99%
“…Table presents a current literature review on the association between vitamin D and breast cancer mortality . This review evaluated recent meta‐analyses, prospective cohort studies, and case‐control studies from 2014 to 2018.…”
Section: Vitamin D and Breast Cancer Mortalitymentioning
confidence: 99%
“…The triple‐negative subtype is a more aggressive cancer with worse disease‐specific outcomes than other breast cancer subtypes because of distinct molecular subtypes that respond differently to chemotherapy and targeted agents . The studies by de Sousa Almeida‐Filho et al in 2016 and Viala et al in 2018 found that vitamin D deficiency and insufficiency in women were significantly associated with triple‐negative breast cancer (Table ) . Furthermore, Viala et al hypothesized that vitamin D deficiency may clinically affect tumor treatment response given the VDR role in proliferation, apoptosis, and angiogenesis …”
Section: Vitamin D and Breast Cancer Mortalitymentioning
confidence: 99%
See 1 more Smart Citation